Pengaruh Penambahan Divinil Benzena (Dvb) Pada Kopolimerisasi Kationik Eugenol-Dvb Dan Sifat Pertukaran Kation Kopoligaramnya = The Effect Of Divinylbenzene (Dvb) Addition To Eugenol-Dvb Cationic Copolymerization And Its - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT Cationic copolymerization between eugenol--divinylbenzene (DVB) with boron trifiuoride diethylether as catalyst at room temperature without media under nitrogen atmosphere has been investigated. The products of polymerization were a mixture between poly(eugenol-co-DVB) and poly(isoeugenol-co-DVB), due to isomerization and copolymerization. The analysis of the number-average molecular weight (M,, ) of copolymer by vapour pressure osmometer (VPO) showed that the increasing of mole of DVB increased the M,, of copolymer. A copolymer of 12% of DVB gave the highest molecular weight, Mn = 3821.17 g mole'. Its melting point was 85.2 Â°C. The copolymer was converted to Na-poly(isoeugenol-co-DVB), K-poly-(isoeugenol-co-DVB), and Ca-poly(isoeugenol-co-DVB) by addition of base, respectively. Ca-poly(isoeugenol-co-DVB) was insoluble in water while Na- and K-poly(isoeugenol-co-DVB) were soluble in water. Subsequently, Ca-poly(isoeugenol-co-DVB) was checked as cationic exchanger by addition of NaCI. Analysis with Atomic Absorption Spectroscopy showed that 3.49 mmole Cal4 could be exchanged with 1t31 mmole Na' in 1 g of copolymer. The structure of poly(isoeugenol-co-DVB), Na-poly(isoeugenolco-DVB), K-poly(isoeugenol-co-DVB), and Ca-poly(isoeugenol-coDVB) were . analized by IR, UV Spectrophotometer and 1F1 NMR Spectrometer.